CFD analysis of cyclone separator used for fine filtration in separation industry - Katare, P.; Krupan, A.; Dewasthale, A.; Datar, A.; Dalkilic, A. S. (ELSEVIER, 2021)
This research is based on industrial application of hydrocyclones for fine filtration. The purpose of this research is to design a hydrocyclone which can be used in the filtration system of cleaning machines and to analyze the performance in terms of efficiency through software for computational fluid dynamics. The hydrocyclone is designed to filter particles of 10-15 mu m with minimum operating cost and without the use of consumables for filtration. In the literature studied, researchers used empirical formulae to model hydrocyclones with a two dimensional approach. The results will be more accurate through the use of CFD with three dimensional entities. The results of the simulation show that pressure increases from the center toward the wall. The maximum and minimum pressures were found to be 9.76-04 Pa and 4.62-04 Pa. The velocity inside the cyclone initially increases then decreases from the center toward the wall. The maximum and minimum values of velocity were found to be 12.5 m/s and 0.55 m/s respectively. The solution of the model shows that the hydrocyclone is capable of producing the desired vortex of the water flowing inside it. The efficiency obtained from these results is 76.19%. This study can be considered the primary stage for validating the use of hydrocyclones in industry.
Keywords: CFD; Hydrocyclone; Filtration; Non-consumable; Modelling; PERFORMANCE; DESIGN; MODELS; FLOW; Thermodynamics